The Epistemological Aspect of Ibn Al-Haytham’s Scientific Thought (Sains Humanika, 2016)
The discussions on epistemology are closely related to the source and methodology of obtaining knowledge. Today’s modern scientific methodology which is driven by logical positivism philosophy lay too much importance on data that can be observed by the senses and is rational to the mind. Therefore, it have a few differences from the Islamic epistemological framework which are value driven in process. However, it was said that Ibn al-Haytham is one the earliest Muslim scholars to base his research on scientific methods. The question is how Ibn al-Haytham obtains scientific knowledge? Does it fit into Islamic epistemological framework? Hence, this article intends to identify the epistemological aspects of Ibn al-Haytham’s scientific thoughts by using the content analysis method. The findings showed that Ibn al-Haytham’s scientific epistemology is based on reflection on the verses of al-Qur’an, belief in God’s law (sunnatullah) of nature, observation by the senses, cognitive reasoning, and intuition. Therefore, the source of knowledge pertaining to Ibn al-Haytham’s scientific thoughts is integrated as what shown in the discussion of Islamic epistemology.
Keywords: Ibn al-Haytham; scientific; thought; God's law; epistemology